Late Quaternary sequence stratigraphy and modern sedimentary processes of the northeastern shelf off the Mekong River Delta - Nguyen Trung, Thanh; Bui Viet, Dung; Tran, Nghi; Paul Liu, J.; Nittrouer Charles, A.; David DeMaster, J.; Nguyen Cong, Thanh; Nguyen Kim, Dung; Hoang Van, Long; Ngo Thanh, Nga; et al. (Vietnam Journal of Earth Sciences, 2026)
Research on Late Quaternary sequence stratigraphy of the northeastern shelf off the Mekong River Delta provides critical insights into the evolution of depositional systems in response to global sea-level changes. The integration of sediment stratigraphic frameworks with observations of recent sediment accumulation and transport helps predict the future development of the Mekong River Delta. In this study, seismic and sediment data collected from six cruises (2004−2015) on the inner-middle shelf were processed and interpreted. Two depositional sequences were identified from high-resolution seismic data, designated SQ1 and SQ2. The depositional sequence SQ2 consists of a transgressive systems tract (TST2) and a regressive systems tract (RST2) identified on the middle shelf. The depositional sequence SQ1, overlying SQ2, comprises a transgressive systems tract (TST1) and a highstand systems tract (HST1), developed during the post-LGM transgression after 19.6 ka. Analysis of SQ1 and SQ2 shows that regressive sediments prevail over transgressive sediments throughout a full fourth-order sea-level cycle (120 ka). Under modern conditions of high relative sea-level rise, spatial variability in sediment accumulation rates from the subaqueous Mekong River Delta to the middle shelf is controlled by hydrodynamic forcing, continental shelf gradient, and variations in sediment transport distance from river mouths: < 2 cm/y on the topset; 1 to > 10 cm/y on the foreset, with an overall tendency to decrease downslope; < 0.5 cm/y on the bottomset-middle shelf. Sediment accumulation rates are relatively low on the middle shelf. Furthermore, the distribution and characteristics of seabed surface sediments indicate that suspended sediment transport across the middle shelf from west to east along the paleo-Dong Nai River, under the influence of the southwest monsoon, reaches the deep sea. Regulation of sequence stratigraphy and modern sediment processes indicates that the present subaqueous Mekong River Delta has reached the limit of seaward progradation and is gradually shifting to retrogradation.